An Algorithmic Approach for and Special Characteristics of Veno-Venous Extracorporeal Life Support in Patients With Severe Asthma Attack: A Case Report and Review of the Literature - HUANG, Linna; ZHAN, Qingyuan (Archives of Clinical and Biomedical Research, 2019)
Little is known about the indicators and special characteristics of veno-venous extracorporeal life support (VV-ECLS) in patients with a severe asthma attack. We included a new case with near-fatal asthma (NFA) in a medical intensive care unit (MICU). Cases with severe asthma attack requiring VV-ECLS from 1980 to 2018 from the literature were added. The general information, laboratory examinations, treatments and outcomes were summarized. There were seventeen cases with severe asthma attack supported with VV-ELCS from the literature, including our case; six of them received extracorporeal CO2 removal (ECCO2R). The average age of the patients was 37 (±18) years, and only three had an underlying disease. Among the seventeen patients, most had a history of prior exacerbations and improper therapies before the current exacerbation, for which there were eleven (64.7%) and nine (52.9%) patients, respectively. As high as fourteen patients (82.4%) had a combination of complications related to asthma pre-ECLS. The most common complication was severe and refractory acidosis. Arterial blood gas analysis values and respiratory mechanics improved significantly post-ECLS. The average blood flow and gas flow of the patients receiving VV-ECLS were 2.3 (±1.2) L/min and 4.0 (±2.6) L/min, respectively. The mean duration of ECLS was 48 (35-96) hours. Complications related to ECLS occurred in 35.3% of the patients, among which hemorrhage was the high prevalence (23.5%). An algorithmic approach to VV-ECLS was described for a patient with a history of prior exacerbations and improper therapies that should be actively supported by ECLS once he becomes unresponsive to maximal therapies or presents with a combination of severe complications. Considering the short duration and the high risk of haemorrhage, anticoagulation without heparin might be a choice.